Preliminary studies on the performance of N'dama and West African Shorthorn cattle in the humid forest zone of Ghana - Tackie, N.O. (1982)
The reproductive performance of N'Dama and West African Shorthorn cattle are examined. Reproductive records of herds kept at Kumasi University farm were analysed. Calving interval and calving percentages varied between both breeds: N'Dama had 498.0 days and 74.2 percent and West African Shorthorn 463.0 days and 60.2 percent, respectively. N'Dama had a productivity index of 82.5 percent per cow per year while West African Shorthorn had 49.6 percent.